Achievements of Technology Teachers` Professional Development Resulted From an International Cooperation - Haskova, Alena; Hodal, Peter; Merode, Dirk Van (Communications - Scientific letters of the University of Zilina, 2018)
In the period of the years 2013 - 2017 an international project focused on modernization of tertiary education in Ukraine, Armenia, and Georgia (supported by the European Union in the framework of the TEMPUS program) was carried out. The main goal of the project was to ensure the quality of teaching technical subjects by providing practically oriented syllabi and modules in the embedded system environment and by creating remote laboratories in the target institutions. In accordance with the main goal, great attention was also paid to the professional development of teachers who have been teaching the relevant technology subjects at the concerned higher education institutions. In the paper its authors discuss issues of the evaluation of teachers’ competencies in general, describe ways of improvement and development of technical subject teachers’ professional competencies in the background of the carried out project, and present results of an analysis aimed at the assessment of the project results achieved with regard to the technical subject teachers.